Pentingnya Pengetahuan Mengenai Anti Korupsi pada Generasi Muda Indonesia Melalui Pembelajaran Pancasila - Dhea Ananda Riandy Putri; Widi Srihayuning; Ika Yulianingsih; Ilham Hudi; Mega Aulia Putri; Melisa Diana Putri; Gustriani Putri (International Forum of Researchers and Lecturers, 2025)
Corruption is one of the biggest challenges facing Indonesia, especially in building a government that is transparent and has integrity. The younger generation plays an important role in breaking the chain of corruption through understanding the values of integrity taught from an early age. This article aims to highlight the importance of knowledge about anti-corruption in the younger generation through learning Pancasila. This research uses a literature review method with analysis of related literature. The research results show that learning Pancasila can be an effective means of instilling anti-corruption values. Then by cultivating and forming an anti-corruption character and mentality among the younger generation who will be able to emphasize anti-corruption values which can become a prevention of criminal acts of corruption in Indonesia. Furthermore, the younger generation has the potential and role as an agent of change in the progress of a nation. Through anticorruption education, it can later foster an anti-corruption culture and be able to increase legal awareness of the younger generation. It is also very important to instill legal values in the younger generation.